Covalent Assembly of Two‐Dimensional COF‐on‐MXene Heterostructures Enables Fast Charging Lithium Hosts - Guo, Dong; Ming, FangWang; Shinde, Digambar B.; Cao, Li; Huang, Gang; Li, Chunyang; Li, Zhen; Yuan, Youyou; Hedhili, Mohamed N.; Alshareef, Husam N.; Lai, Zhiping (Advanced functional materials, 2021)
2D heterostructured materials combining ultrathin nanosheet morphology, defined pore configuration, and stable hybrid compositions, have attracted increasing attention for fast mass transport and charge transfer, which are highly desirable features for efficient energy storage. Here, the chemical space of 2D–2D heterostructures is extended by covalently assembling covalent organic frameworks (COFs) on MXene nanosheets. Unlike most COFs, which are generally produced as solid powders, ultrathin 2D COF‐LZU1 grows in situ on aminated Ti3C2Tx nanosheets with covalent bonding, producing a robust MXene@COF heterostructure with high crystallinity, hierarchical porosity, and conductive frameworks. When used as lithium hosts in Li metal batteries, lithium storage and charge transport are significantly improved. Both spectroelectrochemical and theoretical analyses demonstrate that lithiated COF channels are important as fast Li+ transport layers, by which Li ions can be precisely nucleated. This affords dendrite‐free and fast‐charging anodes, which would be difficult to achieve using individual components. Nanoporous 2D MXene@COF heterostructures are synthesized through the covalent assembly of COF‐LZU1 with an interface‐initiated imine bonding. MXene@COF exhibits high crystallinity, stability, and hierarchical porosity. The ordered 2D channels and uniform nucleation sites boost the Li deposition kinetics, resulting in dendrite‐free and fast‐charging lithium metal batteries.